(untitled) (Praxis Educativa, 2012)
In the area of Pedagogy, the problem of the dicotomies: equality-unequality; diversity-homogenity, has brought a wide variety of debates and has given place to interesting papers that help understand its complexity and give meaning to the necesity of elucidating these questions In this sense, the intention of our work, is to contribute with some conceptual elements that could be useful to set some ideas about the mentioned dualities and at the same time, support practices facing these confl icts and integrate them into a wider scheme making a commitment of action in the classrooms. To make a brief socio political analysis of our country, we focus in the real possibilities of teaching at school, from a political cultural approach which recognizes social diff erences, considers diversity, and proposes –in the complexity of a classroom cultural production with its particular histoies, experiencies, and multicultural languages– to build a cultural net able to promote critical refl ective learning with a democratic training that gives citizens equality of opportunities.